GABA receptor antagonism elicits feeding in the septohypothalamic nucleus - Gabriella, Ivett; Nambiar, Vandana; Kuang, Chlinton; Mukundan, Abinanda; Dang, Jonathan; Venkatraghavan, Aneerudh; Stanley, B. Glenn (Frontiers in Behavioral Neuroscience, 2025)
IntroductionCurrent rates of obesity and eating disorders have been steadily increasing, highlighting the importance of understanding the neural circuits of eating. This study explores the potential role of an understudied brain region, the septohypothalamic nucleus (SHy), in feeding control. Based on a serendipitous observation, we hypothesized that central injections of gamma-aminobutyric acid (GABA) receptor antagonists in the SHy would elicit feeding.MethodAdult male Sprague-Dawley rats (n = 39) were microinjected with a vehicle or GABAA receptor antagonists (bicuculline or picrotoxin) or a GABAB receptor antagonist (2-(S)-(+)-2-hydroxy-saclofen [2-OH saclofen]). Food and water intakes were measured at 1, 2, 3, and 24 h after injection, and behavioral responses (sleeping, resting, locomotor activity, vigorous activity, and grooming) were measured for 1 h.ResultResults showed increased food intake after bicuculline (p < 0.001) and picrotoxin (p = 0.03) injections during the 2nd and 3rd hours compared to controls. In addition, we found increased food intake 1 hour after 2-OH saclofen injections (p < 0.001). As for other behaviors, all three of the drugs suppressed resting (bicuculline: p < 0.001; picrotoxin: p < 0.001; 2-OH saclofen: p < 0.01) and increased locomotor activity (bicuculline: p < 0.001; picrotoxin: p < 0.001; 2-OH saclofen: p = 0.02).DiscussionOur findings suggest that GABAA or GABAB receptor deactivation by antagonists elicited eating with a delayed effect and increased general arousal in rats. These findings collectively suggest that SHy neurons expressing GABAA and/or GABAB receptors are elements of a neurocircuit that participates in the regulation of feeding.